Internalisasi Nilai Budaya Lokal Kupang Dalam Interaksi Komunikatif Mahasiswa BIPA 2 - Indri Jurikhe Pandie; Anas Ahmadi; Agusniar Dian Savitri (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This study aims to analyze the internalization of Kupang’s local cultural values in the communicative interactions of Level 2 BIPA students and to examine the students’ responses regarding the relevance and success of instilling these cultural values. As a multi-ethnic region with more than 35 ethnic groups, the city of Kupang offers a rich and complex communicative environment, making it a relevant context for BIPA learning based on local culture. This study employs a qualitative approach using a literature review method. The results indicate that the internalization of Kupang’s cultural values such as the value of brotherhood (beta-ale), mutual cooperation, and age-based etiquette occurs through contextual and authentic communicative interactions. Students who were directly exposed to local cultural values in learning activities demonstrated improved intercultural competence and cross-cultural communication skills. This study recommends the development of BIPA teaching materials that systematically integrate Kupang’s local wisdom.